PENGARUH KEGIATAN EKSTRAKURIKULER TERHADAP KEMAMPUAN PEMAHAMAN MATEMATIS SISWA DI SMP NEGERI 1 NGAMPRAH - Zakiyah, Siti; Kur'aeni, Dinda Nur; Halawatul, Syifa; Rahayu, Gustiani; Damiyanti, Yuniar; Hidayat, Wahyu (IKIP Siliwangi, 2018)
Extracurricular activity is an activity related to co-curricular and intracuticular in school. One of the main objectives of this extracurricular activity as a place for students who have the interest to follow the activity. This activity can form a positive attitude of students. This study aims to determine the effect of extracurricular activities on the ability of students' mathematical understanding in SMP Negeri 1 Ngamprah. The research method used is a quantitative method with the help of IBM SPSS Statistic 24 applications. The sample used in this study is the students of class VIII SMP Negeri 1 Ngamprah who follow extracurricular and do not follow extracurricular. Students who follow extracurricular become experimental class and students who do not follow extracurricular become control class. The results of this study are the ability of students' understanding of mathematics in SMP Negeri 1 Ngamprah who follow extracurricular and do not follow extracurricular have significant differences. Students who follow extracurricular activities have a better understanding of mathematics than students who do not follow extracurricular activities. Seen based on the existing data obtained the average of the experimental class is 41.8 and the control class 34.4. It gives some influence to the students' comprehension ability that is, giving positive values and good personality for the students, such as thinking creatively and wisely in determining the action, attitude, and decision.